2012
DOI: 10.1152/ajplung.00018.2012
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 knockout mice exhibit airway hyperreactivity

Abstract: Although caveolins have been found in endothelium and epithelium (where they regulate nitric oxide synthase activity), their role in smooth muscle is still under investigation. We and others have previously shown that caveolae of human airway smooth muscle (ASM), which express caveolin-1, contain Ca 2ϩ and force regulatory proteins and are involved in mediating the effects of inflammatory cytokines such as TNF-␣ on intracellular Ca 2ϩ concentration responses to agonist. Accordingly, we tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 68 publications
1
34
0
Order By: Relevance
“…Thus it could be reasoned that caveolin-1 contributes to the balance between contractile vs. proliferative phenotype of ASM in the context of inflammation but in either fashion enhance airway changes in asthma for example. Unfortunately, this distinction may not be as clear cut, as evidenced by a recent report that airways of caveolin-1 knockout mice are actually more responsive to methacholine challenge, a feature exacerbated with ovalbumin sensitization and challenge (7). However, airway thickness as well as markers of cell proliferation are increased in caveolin-1 KO mice, consistent with other in vitro data on cell proliferation.…”
Section: L918supporting
confidence: 58%
See 2 more Smart Citations
“…Thus it could be reasoned that caveolin-1 contributes to the balance between contractile vs. proliferative phenotype of ASM in the context of inflammation but in either fashion enhance airway changes in asthma for example. Unfortunately, this distinction may not be as clear cut, as evidenced by a recent report that airways of caveolin-1 knockout mice are actually more responsive to methacholine challenge, a feature exacerbated with ovalbumin sensitization and challenge (7). However, airway thickness as well as markers of cell proliferation are increased in caveolin-1 KO mice, consistent with other in vitro data on cell proliferation.…”
Section: L918supporting
confidence: 58%
“…Furthermore, signaling mechanisms within ASM itself could be involved. For example, caveolin-1 can inhibit proliferation (7,89,92), whereas the SOCE mechanisms STIM1 and Orai1 can enhance TGF-␤1-induced proliferation (79) (Fig. 5).…”
Section: L921mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect on ASM force generation and contractility is mimicked in animal models following airway sensitization (Stephens et al 2003; Aravamudan et al 2012), or following cytokine exposure in ASM muscle strips (Fig. 2), or in lung slice preparations (Fig.…”
Section: Cytokine Enhancement Of [Ca2+]cyt and Force Responses In Asmmentioning
confidence: 80%
“…Notably, caveolin-1 suppression has been associated with the proliferative airway smooth muscle phenotype. 50 Of particular relevance to this study is also the fact that caveolin-1 has been shown to confer cell polarity, 51 which makes our finding that caveolin-1 is upregulated in more polarized cells, specifically those on soft ANFS, interesting. Finally, we also found that the levels of profilin-2 were upregulated in cells on nanopatterned substrata (Fig.…”
Section: Potential Mechanistic Processes Involved In Cell-sensing Of mentioning
confidence: 83%